2015
DOI: 10.1111/1365-2435.12518
|View full text |Cite
|
Sign up to set email alerts
|

Multiple strategies for drought survival among woody plant species

Abstract: Summary1. Drought-induced mortality and regional dieback of woody vegetation are reported from numerous locations around the world. Yet within any one site, predicting which species are most likely to survive global change-type drought is a challenge. 2. We studied the diversity of drought survival traits of a community of 15 woody plant species in a desert-chaparral ecotone. The vegetation was a mix of chaparral and desert shrubs, as well as endemic species that only occur along this margin. This vegetation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 48 publications
6
91
0
Order By: Relevance
“…Overall, the model analysis presented here demonstrates that multiple measurable drought resistance traits can be integrated into a consistent and thermodynamically reliable formal framework to define drought‐induced mortality (Pivovaroff et al . ). This modelling approach must be validated carefully against the temporal dynamics of water potential, hydraulic conductance, data for embolism proper, and experimental and field mortality for different species.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, the model analysis presented here demonstrates that multiple measurable drought resistance traits can be integrated into a consistent and thermodynamically reliable formal framework to define drought‐induced mortality (Pivovaroff et al . ). This modelling approach must be validated carefully against the temporal dynamics of water potential, hydraulic conductance, data for embolism proper, and experimental and field mortality for different species.…”
Section: Resultsmentioning
confidence: 97%
“…For example, when water was available and atmospheric demand was low, such as during cool and wet winter climatic conditions, midday water potentials converged among study species (Figure ). However, when temperatures warmed and water became limiting, the diversity of drought response mechanisms associated with these traits led to a wide range of minimum seasonal water potentials (Pivovaroff, Pasquini, et al, ). For example, deeply rooted, drought deciduous, and riparian species had high (less negative) minimum seasonal water potentials and less resistant xylem.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in a southern California native shrubland found that shallow‐rooted species with cavitation resistant xylem experienced the highest mortality levels due to drought, whereas deeply rooted species with xylem vulnerable to cavitation had lower mortality levels (Venturas et al, ). This differential mortality among co‐occurring species due to varying drought survival strategies (Pivovaroff, Pasquini, et al, ) may result in changes in community composition and ultimately biodiversity loss. However, predicting mortality remains a challenge for vegetation models due to wide variation in premortality physiological changes among species (Anderegg et al, ; Garcia‐Forner, Sala, Biel, Save, & Martinez‐Vilalta, ; McDowell, ; McDowell et al, ; Pivovaroff, Pasquini, et al, ; Sevanto, Xu, & Way, ).…”
Section: Introductionmentioning
confidence: 99%
“…This fundamental understanding of water uptake and transport from roots to shoots underlies the utility of stable isotopes in plant water uptake investigations17. While many site-based studies have now been completed18192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114…”
mentioning
confidence: 99%